Development of Metamaterial Industry in China: Analysis and Suggestions - Ji Zhou; Lianmeng Zhang (中国工程科学)
As a class of artificially structured material that exhibits extraordinary properties not available or not easily obtainable in nature, metamaterials provide transformative technologies for many application fields. Now the implementation of new principles and functions regarding metamaterials has entered an explosive period, and the industrial chain has entered a nascent stage; meanwhile, large-scale engineering of metamaterials has entered a bottleneck period. This study summarizes the conceptual evolution process of metamaterials, outlines the research progress and development trends of metamaterials from both international and domestic perspectives, and analyzes the industrialization progress of metamaterials from three aspects: industrialization direction, industrial chain pattern, and industrial development strategy. The challenges of the metamaterial industry, involving preparation technology, testing and characterization technology, engineering technology, industrial chain, and research and development personnel, are highlighted. The new development opportunities brought by AI to the metamaterial industry were discussed from two perspectives: application of artificial intelligence (AI) in metamaterial design and application of metamaterials in the evolution of AI. It is recommended to focus on key application needs for major project layout, establish a national platform for metamaterial preparation, big data, and design, form a national innovation consortium, and promote interdisciplinary talent cultivation, thereby accurately promoting the high-quality development of China's metamaterial industry in the medium and long term.